A new species of Dysaphis Borner from Iran and Italy, and a new subspecies from Iran. (Bollettino di zoologia agraria e bachicoltura, 2024)
During the latter part of the summer of 1968 I received some samples of Dysaphis for study from Dr Hille Ris Lambers. These had been collected in Iran by Dr R. van den Bosch, and consisted mainly of samples of the very difficult D. foeniculus group. One species, from Lepidium draba ( = Cardaria draba [L.] Desv. of Clapham, Tutin & Warburg) exhibited characters sufficient to separate it from those other members of the group known to me. This species was subsequently collected also from the same host at Ventimiglia, Italy, by Dr Hille Ris Lambers, and he kindly sent me this material also for comparison. No species of Dysaphis has hitherto been described from C. draba. NEVSKY (1929) keyed a species Dentatus capsellae from radical leaves of Capsella, but did not give a full description of it. SHAPOSHNIKOV (1964) also keyed this species, ascribing it to Mordvilko, but gave no morphological diagnosis. I have been unable to trace any reference to an originai description by Mordvilko, and since NEVSKY's key uses no characters adequate to separate the species from other members of the foeniculus complex I consider that it is desirable to describe the aphids from• draba as a new species.